PEACE ENFORCEMENT DAN ORGANISASI INTERNASIONAL Kontradiksi Perlindungan Masyarakat Sipil dan Implementasi Resolusi 1973 Dewan Keamanan PBB Oleh NATO Pada Konflik Libya 2011 - , Fauzi; , Drs. Samsu Rizal Panggabean, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Handling of armed conflict through the concept of peace enforcement is still far from success. Especially with the actors of international organizations engaged on the basis of the interests of members in resolving the conflict. This occurred in the handling of the Libyan conflict with NATO involvement execute the mandate of Resolution 1973 which set the resolution of the UN Security Council as Libya's settlement of the armed conflict in 2011. Failure to implement UN Security Council Resolution 1973 has seen since the beginning of the political process that is carried through with meetings between state leaders to discuss the handling of the Libyan conflict in 2011. So through these meetings, the strategy and tactics of the implementation of Resolution 1973 by the NATO decision to adjust the results of the state leadership. Not to mention, in the content of Resolution 1973 there is a contradiction between the implementation of No Fly Zone (NFZ) and protection against civil society. Basically, NFZ is monitoring the use of military air resulting in civilian casualties. Implementation of the NFZ in Libya that NATO over military air should ensure Qaddafi and other countries that want to help the Libyan leader, is not used to threaten the safety of Libyan civilians. Influence state policy is incorporated against Qaddafi, NATO made in carrying out the military operation in Libya in support of the group of the National Transitional Council (NTC) to cripple Qaddafi. Theories and concepts used in this study is the concept of peace enforcement and international organizations. While the research methods used to address the handling of the Libyan conflict by NATO is a qualitative method that is sourced from books, opinions expressed during Libya conflict. The results of this study show the strong influence of the state interest underlying the actions undertaken NATO as an international organization that is leading the legitimacy of military operations Libyan conflict resolution. So that there are contradictions between the protection of civilians a priority the enactment of Resolution 1973 by the UN Security Council with NATO conducted implementation. Keyword: Peace Enforcement, International Organization, No Fly Zone, NATO, Libya Conflict, Resolution 1973, Protection of Civilian